Agricultural Efficiency of OIC Countries: Addressing SDG-2 Output - Prakoso, Muhammad Fajar Dito (SMART Insight, 2025)
The research method employs a DEA approach to measure the relative efficiency of each country in utilizing agricultural inputs to produce the desired outputs. The analysis was conducted to determine the annual average efficiency, the variation between countries, and the overall ranking based on the average efficiency over the study period. The analysis is further extended by measuring productivity using the Malmquist Productivity Index (MPI). The results reveal that several OIC countries, such as Egypt, Uzbekistan, and Yemen, consistently achieved full efficiency during the study period, while countries like Uganda and Afghanistan recorded persistently low efficiency levels. The MPI results show that overall productivity growth in OIC agriculture was driven mainly by technological progress rather than efficiency improvements. These findings indicate heterogeneous performance and underline the importance of technology adoption and governance quality in driving agricultural transformation. The results provide actionable insights for policymakers to design strategies enhancing agricultural efficiency, including regional cooperation, technological innovation, and institutional reforms to strengthen food security systems in OIC member states.